2008
DOI: 10.3168/jds.2007-0212
|View full text |Cite
|
Sign up to set email alerts
|

Quarter-Level Analysis of Subclinical and Clinical Mastitis in Primiparous Heifers Following the Use of a Teat Sealant or an Injectable Antibiotic, or Both, Precalving

Abstract: This study investigated the effect of infusion of a bismuth subnitrate teat canal sealant or an injectable antibiotic, or both, in heifers on the cure of existing intramammary infection (IMI), incidence of new IMI, prevalence of postcalving IMI, and incidence of clinical mastitis in the first 2 wk postcalving at the quarter level. Heifers (n = 1,067) in 30 seasonally calving, pasture-fed dairy herds were randomly assigned at the heifer level to 1 of 4 treatments (no treatment; 3 intramuscular injections of 5 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 37 publications
7
27
0
9
Order By: Relevance
“…These facts reflect positively on the reduction of somatic cell count (SCC) and cases of clinical mastitis in the first 100 days of lactation. The same effects were observed for postpartum heifers that received internal seals during pre-partum (Parker et al 2007(Parker et al , 2008.…”
Section: Introductionsupporting
confidence: 67%
“…These facts reflect positively on the reduction of somatic cell count (SCC) and cases of clinical mastitis in the first 100 days of lactation. The same effects were observed for postpartum heifers that received internal seals during pre-partum (Parker et al 2007(Parker et al , 2008.…”
Section: Introductionsupporting
confidence: 67%
“…Following sampling or infusion, 0.5% effective iodine was applied by manual spraying to all teat ends. Technicians administered the first treatment of tylosin and then left labeled doses of tylosin for the remaining 2 treatments for farm staff to administer (Parker et al, 2008).…”
Section: Examplementioning
confidence: 99%
“…This reduction was due to reduction of new intramamammary infections. There was no cure of already infected quarters (Parker et al, 2008). However, both Schukken et al (1991) and Lam et al (1997) identified an association between the use of iodine PMTD and more clinical coliform mastitis.…”
Section: Discussionmentioning
confidence: 95%